Análisis de la implementación de hongos micorrizicos nativos sobre el desarrollo y producción de híbridos de maíz duro - Carrasco Contreras, Guillermo Andrés (2017)
SUMARY The effectiveness of mushrooms mycorrhiza was evaluated on the development and yield of corn hard grain (Zeamays L.). The present work demonstrated the incidence of the mushrooms about the readiness of nutritious in the cultivation, demonstrating that the different concentrations with more number of spores have an effect on the production. Dispersed information on investigation works in this biofertilizantes class, motivated the collection and classification of this in a technical way, based on the importance of the articles. The efficiency of mushrooms mycorrhiza in the infection radicular and their contribution to improve the quality of plants, they demonstrate the physiologic and ecological benefits exercised by this group of microorganisms. Positive answers exercised by the native mycorrhiza, believe the necessity to have banks specific germoplásmicos for the Ecuadorian Humid Tropic and to select goods of efficient mushrooms dedicated to the inoculantproduction for agricultural and forest species of economic importance.